Learning Mixed Arithmetic Operations Using WhatsApp Groups for Islamic Elementary School Students - Thoriq, Muhammad; Sakti, Asri Wibawa; Azizah, Nissa Nur (Indonesian Journal of Teaching in Science, 2023)
The purpose of this study is to show whether WhatsApp groups can be one of the media for learning mixed arithmetic operations mathematics during the online learning process. This study uses a quantitative approach to the pre-experimental design method (one group pretest-posttest). The research subjects were 16 students of class VI Islamic elementary school. Students' knowledge of mixed arithmetic operations, when given a pretest, was 55.6%. After learning mixed arithmetic operations using the WhatsApp group, the post-test results increased to 57.5%. Based on these results, there was an increase in students' knowledge of 1.9%. This is because students understand learning using WhatsApp groups. So learning to use WhatsApp groups can slightly increase knowledge in mixed arithmetic operations.